Functional Magnetic Resonance Imaging of Effects of a Nicotinic Agonist in Schizophrenia - Tregellas, Jason R (Nature Publishing Group, 2010)
3-(2,4-Dimethoxybenzylidene)-anabaseine (DMXB-A) is a partial agonist at α7-nicotinic acetylcholine receptors and is now in early clinical development for treatment of deficits in neurocognition and sensory gating in schizophrenia. During its initial phase 2 test, functional magnetic resonance imaging (fMRI) studies were conducted to determine whether the drug had its intended effect on hippocampal inhibitory interneurons. Increased hemodynamic activity in the hippocampus in schizophrenia is found during many tasks, including smooth pursuit eye movements, and may reflect inhibitory dysfunction. Placebo and two doses of drug were administered in a random, double-blind crossover design. After the morning drug/placebo ingestion, subjects underwent fMRI while performing a smooth pursuit eye movement task. Data were analyzed from 16 nonsmoking patients, including 7 women and 9 men. The 150-mg dose of DMXB-A, compared with placebo, diminished the activity of the hippocampus during pursuit eye movements, but the 75-mg dose was ineffective. The effect at the 150-mg dose was negatively correlated with plasma drug levels. The findings are consistent with the previously established function of α7-nicotinic receptors on inhibitory interneurons in the hippocampus and with genetic evidence for deficits in these receptors in schizophrenia. Imaging of drug response is useful in planning future clinical tests of this compound and other nicotinic agonists for schizophrenia.